Efektivitas Peran Kepolisian Dalam Penerapan Restorative Justice Terhadap Kasus Pelecehan Seksual Oleh Anak di Batam - Aisyah, Siti; Alhakim, Abdurrakhman; Tantimin, Tantimin (Morality: Jurnal Ilmu Hukum, 2024)
Abstract: Restorative justice is another step in criminal justice that focuses on a method that integrates offenders on one side with victims, as well as the public, into a unity to find solutions and restore good relationships within their community. The purpose of this paper is to discuss the rules related to Restorative Justice in the law and the effectiveness of implementing Restorative Justice in handling cases of sexual abuse committed by children in the city of Batam. The method used in this paper is normative-empirical. The implementation of restorative justice arises from agreements among the parties involved in criminal cases, without coercion from the police. The use of restorative justice methods to address criminal issues in the legal area of Polresta Barelang Batam is considered highly effective because it can control the desires of all parties involved in criminal cases. This will prevent the emergence of problems that commonly arise when the desires of a party are not accommodated.